Online delivery of oral HIV pre‐ and post‐exposure prophylaxis: findings from the ePrEP Kenya pilot - Catherine Kiptinness; Paulami Naik; Tabitha Kareithi; Nicholas Thuo; Phelix Okello; Carlos Culquichicon; Maeve Rafferty; Samira Abdulrashid; Edwin Jomo; Nicky Nyamasyo; Tony Wood; Rouella Mendonca; et al. (Journal of the International AIDS Society, 2025)
Abstract Introduction The expansion of telecommunication networks and smartphones in many African countries could be leveraged to deliver HIV prevention products directly to consumers. In collaboration with a private e‐commerce platform and online pharmacy in Kenya, MYDAWA, we piloted a new model of HIV pre‐ and post‐exposure prophylaxis (PrEP/PEP) delivery. Methods In the ePrEP Kenya pilot (NCT05377138), individuals living in Nairobi and Mombasa Counties could complete a free telehealth visit with a remote clinician to assess eligibility for online PrEP/PEP (i.e. ≥18 years; no medical contraindications). Eligible individuals could order HIV testing services—courier delivered to clients’ choice location—for a fee of 250 KES (∼$2 USD) for self‐testing or 150 KES (∼$1 USD) for provider‐administered rapid diagnostic testing. Following confirmation of clients’ HIV‐negative status (via an uploaded test result image), free PrEP/PEP drugs from government supply were courier delivered with or separately from HIV testing services. Clients paid a delivery fee ≤149 KES (∼$1 USD) per courier visit. Results From October 2022 to December 2023, we screened 2257 individuals and enrolled 1915. Most PrEP/PEP clients were men (63%, 1428/1915), ≥25 years (72%, 1631/1915) and never married (80%, 1796/1915); few had ever used PrEP (3%, 48/1915) or PEP (14%, 263/1915). At enrolment, 227 (12%) were preliminarily eligible for PrEP and 1688 (88%) for PEP. Among PrEP‐eligible clients, 89% (203/227) completed HIV testing and 92% (208/227) received PrEP; among PEP‐eligible clients, 92% (1551/1688) completed HIV testing and 92% (1549/1688) received PEP. Most PrEP/PEP clients completed HIV testing within 6 hours of their telehealth visit (53%, 927/1757) and had drugs delivered with testing services (88%, 1546/1757). Among PrEP clients eligible for follow‐up, 47% (120/256) continued PrEP and 4% (10/256) initiated PEP following PrEP discontinuation. Among PEP clients eligible for follow‐up, 7% (99/1428) repeated PEP use and 6% (83/1428) transitioned from PEP to PrEP.). Conclusions Online PrEP/PEP delivery could expand access to prevention services by reaching individuals not engaged in existing delivery platforms. The uptake of online PEP was five times greater than PrEP, underscoring an unmet demand for PEP and highlighting the potential for online pharmacies to deliver time‐sensitive PEP services.